Academics' Intentions to Use Open Educational Resources (OERs) in Professional Development - Karataş Erinç; Yılmaz Ayşe Bağrıacık; Karataş Serçin; Banyard Phil (Sciendo, 2022)
Introduction: Open educational e-resources (OERs) are one of the informational resources that are openly available to all. Open educational e-resources provide learners with free access to high-quality educational content and materials. Learners should be able to use, read, adapt, and share these resources freely. In this study, we aimed to examine academics' open educational e-resources usage intentions. We also tried to understand behavioral differences by collecting data from two different countries: Turkey and the United Kingdom.